Cultivo de milho verde em sistemas de manejo convencional e conservacionistas em experimento de longa duração - Silva, Jéssica Fernanda da (2022)
Corn cultivation is a practice of great economic growth and rural development in Sergipe, as it provides markets and businesses for family farmers where the climate and soil are favorable to the crop. The use of different soil management systems associated with the use of previous crops can represent a sustainable alternative, improved by the combination of techniques for the economic favoring of vegetable production in corn. The present work has as a problem that incorrect soil management practices lead to low productivity of corn exploration in the state of Sergipe. The objective was to analyze the feasibility of associating different cultivation systems, antecedent cultures and inoculation of bacteria for the cultivation of green corn in a long-term experiment in the State of Sergipe. The variables of a, long duration, field experiment of the cultivation of green corn, implanted in the Experimental Farm of the UFS since 2001, were evaluated. The evaluations correspond to the 19th, 20th and 21st years of cultivation. The experimental design adopted was that of experimental strips with subdivided plots, where the cultivation systems were implanted in the strips: conventional, minimum and no-tillage, and in the subdivided plots the previous crops: sunn hemp, cowpea, pigeon pea and millet. Corn seeds were inoculated with the bacterial inoculants Herbaspirillum seropedicae in the 2019 harvest and with Azospirillum brasilense in the 2020 and 2021 harvests and received different doses of N complementation. Corn productivity was evaluated by quantity and weight of commercial cobs, plant dry weight, total plantchlorophyll content and plant height. Soil chemical parameters (soil fertility parameters) were also evaluated with deformed and physical soil samples (soil density and mechanical resistance to soil penetration) with undisturbed and field samples, respectively. For economic analysis, the structure of the total operational cost of production used by the Institute of Agricultural Economics (IEA) was used. As main results it was obtained that the association between the use of cropping systems, adoption of antecedent cultures and inoculation of Herbaspirillum seropedicae or Azospirillum brasilense favor the productivity of green corn. The most significant results were associated with the minimum tillage and no-tillage systems, the antecedent cultures of sunn hemp and Millet and the inoculation of Azopirillum brasilense. The inoculation of Azospirillum brasilense provides greater economic profitability associated with minimal cultivation and use of cowpea as a background crop. There is need to complement the inoculation with N fertilization, but the nutritional conditions of the soil in conservation systems together with the benefits provided by the antecedent cultures contribute to the reduction of chemical fertilizers usage, providing economic and environmental benefits.